So it follows that a1 d1 u 1 d 1 u 1 0 d1 0 1 d2

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: entry along the the diagonal of the diagonal matrix D. So it follows that: A−1 = D−1 U −1 = D −1 U ∗ 1 0 ··· d1 0 1 ··· d2 = 0 0 ... 0 0 ··· 1 0 0 ∗ U 0 1 dn Thus, using our knowledge of left multiplication with diagonal matrices, we get: [A−1 ]ij = d−1 [U ∗ ]ij = d−1 uji ¯ i i 2 2.1 Schur Triangularization and Consequesnces (continued) Schur’s triangularization theorem 2.1.1 Theorem. (Schur’s Triangularization Lemma) Let A ∈ Mn , with eigenvalues λ1 , λ2 , ..., λn (where multiplicity is counted). Then there exists U ∈ Mn , where U ∗ U = I , such that: A = UT U∗ and λ1 ∗ · · · ∗ 0 λ2 · · · ∗ T = 0 0 ... ∗ 0 0 · · · λn is upper triangular. In other words, every sq...
View Full Document

This note was uploaded on 01/16/2014 for the course MATH 6304 taught by Professor Bernhardbodmann during the Fall '12 term at University of Houston.

Ask a homework question - tutors are online